Economic development - Todaro, Michael P. (New Delhi, 2012)
Economic Development, Tenth Edition, marries the latest thinking in development economics with the clear and comprehensive approach that has been so well received in previous editions. The text places the themes of earlier editions into to day's global setting and introduces current topics such as the Millennium Development Goals, the origins of comparative development, complementarities and coordination failure, growth diagnostics, industrialization strategy, new strategies for poverty reduction, the capabilities approach to well-being, the central role of health, new thinking on the role of cities, the economic character and comparative advantage of nongovernmental organizations in economic development, emerg ing issues in environment and development, and the economics of microfinance. The book also emphasizes the international context for development, including the implications of the rapid pace of globalization and the rise of China, the continuing crisis of sub-Saharan Africa, and the ongoing conflict over funding for debt relief and poverty reduction. Because viewpoints vary regarding which topics in economic development deserve the greatest emphasis, we have structured the presentation of the text so as to provide instructors with considerable flexibility in selecting lecture topics.
Keywords: Economic development